Arnold Schoenberg's A Survivor from Warsaw in Postwar Europe. - Calico, Joy H. (California studies in 20th-century music ;, 2014)
Joy H. Calico examines the cultural history of postwar Europe through the lens of the performance and reception of Arnold Schoenberg's A Survivor from Warsaw-a short but powerful work, she argues, capable of irritating every exposed nerve in postwar Europe. Schoenberg, a Jewish composer whose oeuvre had been one of the Nazis' prime exemplars of entartete (degenerate) music, immigrated to the United States and became an American citizen. Both admired and reviled as a pioneer of dodecaphony, he wrote this twelve-tone piece about the Holocaust in three languages for an American audi.